Pharmacokinetic, efficacy, and safety considerations for the use of antifungal drugs in the neonatal population. (2nd July 2020) - Scott, Briana L.; Hornik, Chi D.; Zimmerman, Kanecia
ABSTRACT: Introduction: Invasive fungal infections are an important cause of morbidity and mortality in infants, particularly in extreme prematurity. Successful systemic treatment requires consideration of antifungal efficacy, safety, and pharmacokinetics, including optimization of dosing in this population. Areas covered: This review summarizes published pharmacokinetic data on four classes of antifungal agents used in the neonatal population. Alterations in absorption, distribution, drug metabolism and clearance in infants compared to adult populations are highlighted. Additionally, pharmacodynamics, safety, and therapeutic drug monitoring are discussed. Recent advancements in neonatal antifungal pharmacotherapies are examined, with emphasis on clinical application. Expert opinion: Over the last two decades, published studies have provided increased knowledge on pharmacokinetic considerations in the neonatal population. Future research should focus on filling in the knowledge gaps that remain regarding the benefits and risks of combination antifungal therapy, the rising use of micafungin for invasive candidiasis given its fungicidal activity against polyene and azole-resistant Candida species and its minimal adverse effect profile, and the need for pharmacokinetic and safety data of broad spectrum triazoles, like voriconazole and posaconazole, in infants. Furthermore, efforts should focus on well-designed trials, including population pharmacokinetic studies, to develop dosing recommendations with subsequent implementation into clinical practice.